Impact of habitat manipulation on the diversity and abundance of beneficial and pest arthropods in sugarcane ratoon - Heri Prabowo; Bambang Tri Rahardjo; Gatot Mudjiono; Akhmad Rizali (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Prabowo H, Rahardjo BT, Mudjiono G, Rizali A. 2021. Impact of habitat manipulation on the diversity and abundance of beneficial and pest arthropods in sugarcane ratoon. Biodiversitas 22: 4002-4010. Sugar production in Indonesia faces several challenges such as infestation of pests and diseases that lead to decline in sugarcane production and productivity. In order to overcome the loss of yields from the presence of pests, alternative new approaches are sought by solving of the problem that can have a sustainable impact by applying habitat manipulation. Habitat manipulation changes the diversity and density of arthropods populations in agro-ecosystem. In the concept of managing agroecosystems with habitat manipulation, it is hoped that the development of agro-ecosystem resilience against pest management will be expected to be suistainable. The results showed that there was an increase in the number of arthropods in the research area for 20 weeks after the management of agro-ecosystems through habitat manipulation. The arthropods in all the traps were dominated by Collembola, Diptera, Coleoptera, Aranea, and Hymenoptera. There were 44 genera that belong to predators and 8 species are belonging to parasitoids. The diversity index of Shannon-Wiener (H '), Simpson Dominance (C) and Species Evenness (E) was not significantly different between treatment and control, but habitat manipulation treatment was able to increase the number of detritivores, predators, parasitoids, and pollinators by 38.81; 43.88; 58.4; and 75.35%. The full role of arthropods in the food chain of the sugarcane ecosystem has been identified and efforts are needed to optimize the role of natural enemies in the agroecosystem to maintain ecosystem stability. Habitat manipulation can increase the number of beneficial insect populations in short run, but it might take time to increase their diversity in agroecosystem.